Fatty acid transport protein inhibition sensitizes breast and ovarian cancers to oncolytic virus therapy via lipid modulation of the tumor microenvironment - Surendran, Abera; Jamalkhah, Monire; Poutou, Joanna; Birtch, Rayanna; Lawson, Christine; Dave, Jaahnavi; Crupi, Mathieu J. F.; Mayer, Justin; Taylor, Victoria; Petryk, Julia; de Souza, Christiano Tanese; Moodie, Neil; et al. (Frontiers in Immunology, 2023)
Adipocytes in the tumour microenvironment are highly dynamic cells that have an established role in tumour progression, but their impact on anti-cancer therapy resistance is becoming increasingly difficult to overlook. We investigated the role of adipose tissue and adipocytes in response to oncolytic virus (OV) therapy in adipose-rich tumours such as breast and ovarian neoplasms. We show that secreted products in an adipocyte-conditioned medium significantly impair productive virus infection and OV-driven cell death. This effect was not due to the direct neutralization of virions or inhibition of OV entry into host cells. Instead, further investigation of adipocyte secreted factors demonstrated that adipocyte-mediated OV resistance is primarily a lipid-driven phenomenon. When lipid moieties are depleted from the adipocyte-conditioned medium, cancer cells are re-sensitized to OV-mediated destruction. We further demonstrated that blocking fatty acid uptake by cancer cells in a combinatorial strategy with virotherapy, has clinical translational potential to overcome adipocyte-mediated OV resistance. Our findings indicate that while adipocyte secreted factors can impede OV infection, the impairment of OV treatment efficacy can be overcome by modulating lipid flux in the tumour milieu.